INVESTIGATION OF GROUNDWATER CONTAMINATION IN SOME SELECTED AREAS OF BOGORO AND ENVIRONS, NORTH-EAST NIGERIA - Yohanna, A.; Musa, N.; Balogun, F. A.; Agada, E. A.; Adamu, A.; Galumje, S. S. (FUDMA Journal of Sciences, 2022)
The quality of drinking water in some selected areas of Bogoro and its Environs in Bauchi State, Nigeria, were investigated in order to assure a continuous supply of clean and safe drinking water for public health protection and analyze the spatiotemporal variation of groundwater quality in the area. A rigorous physical and chemical study of drinking water samples was conducted in some residential and commercial areas. For each water sample collected during dry and wet seasons, a variety of physical characteristics such as pH, turbidity, conductivity, total dissolved solids (TDS), and chemical parameters such as Ca, Na, K, SO24, PO24, F, Cl, Cu, Mg, Fe, and Mn were analyzed. The resulting values for each parameter were compared to the World Health Organization’s (WHO) and European Union (EU) standards. The values of each parameter were found to be within the permissible limits with the exception of Turbidity with an average value of 7.55mg/L, Fluoride (0.52mg/L), Iron 0.69mg/L which were above the permissible limit. The implications of ingestion of these contaminants include Gastro-Intestinal distress, liver or kidney damage with some other health implications. However, in order to assess the total water quality of water in the area, itâ€™s necessary to analyze other potential water contaminations, such as heavy metals, microbiological and radioactive elements, and human body fluids. Based on these findings, itâ€™s recommended that Public health institutions should intensify awareness and enlightenment campaigns to water users on procedures and water treatment techniques.